DESIGN OF WEB-BASED DEATH AND ELDERLY DATA COLLECTION APPLICATION AT MEDAN JOHOR DISTRICT OFFICE - Siregar, Muhammad Awwal Ashari; Sembiring, Boni Oktaviana; Irwan, Dedy (Cattleya Darmaya Fortuna, 2025)
Data collection on deaths and elderly at the Medan Johor Sub-district Office is an urgent need to improve efficiency and accuracy in the data collection process at the government agency. elderly. With the increasing elderly population, it is important for the Medan Johor Sub-district Office to have an efficient and organized data collection system to manage elderly population data in its work area. The manual data collection system that may still be used by the Medan Johor Sub-district Office also has limitations. Manual processes such as filling out paper forms, manual data collection and processing can slow down the data collection process and increase the risk of errors. Therefore, designing a web-based data collection application is the right solution. By implementing a web-based data collection system, these limitations can be overcome by electronic data entry, automatic validation, and real-time data access. The results of this study This application will help improve the accuracy of data on deaths and elderly population, reducing the potential for human error in manual data input.